THE STEREOTYPES OF WOMEN: PATRICK SÜSKIND’S PATRIARCHAL IDEOLOGY AS REPRESENTED IN HIS PERFUME; THE STORY OF A MURDERER - Siska Wati (Vivid: Journal of Language and Literature, 2013)
This research analyzed Patrick Süskind’s patriarchal Ideology as a male author that is presented through the women's character and the storyline of Perfume; the story of murderer.  This analysis applies Feminist Criticism from Millet’s theory: Sexual Politics, which could show a man biased-perspective about women’s inferiority in their works as implies as their strong influence on Patriarchy by way of a writer. This research is an intrinsic analysis which the analysis is processed just limits on storyline and intrinsic element of the work without external factor to be included on. The result of the analysis that researcher find from the novel is a few kinds of negative stereotypes of the female characters’ description. Then, in the analysis of women relation upon male characters in the story, the researcher also finds male characters’ perspective in the plotline, as same as author’s patriarchal ideology about inferiority of women’s ability as innate. This chase strengthens male domination upon women is so blatantly and moreover this novel can be judged as per medium of male author to defend the existence of patriarchal ideology.Keywords: Women’s stereotypes, male author, women representation, sexual politics, patriarchal existence